Manifesto for learning - Collins, Janet (Continuum studies in lifelong learning., 2002)
What makes people learn effectively? What can we do to promote more effective learning?Innumerable researchers have studied these important and urgent questions, yet their findings tend to be fragmentary and disparate. Now Janet Collins, Joe Harkin and Melanie Nind provide the big picture. Drawing on research from all sectors of education the authors show that effective learning depends crucially on a few easily understood principles. These principles hold true regardless of the age or nature of the learner or the context in which the learner is working. Manifesto for Learning explains those pr.